Inflammatory Activity in Patients with Obstructive and Non-obstructive Coronary Artery Disease - N. N. Pakhtusov; A. O. Yusupova; A. S. Lishuta; O. A. Slepova; E. V. Privalova; Yu. N. Belenkov (Рациональная фармакотерапия в кардиологии, 2023)
Aim. To study the levels of pro-inflammatory biomarkers  in patients with obstructive  and non-obstructive coronary  artery disease (CAD), to identify possible differences  for diagnosing the degree of coronary  obstruction.Material and methods. The observational  study included two groups of patients: with non-obstructive (main group,  coronary artery stenosis <50%; n=30) and obstructive  (comparison group,  hemodynamically significant  coronary  artery stenosis according to the results of coronary  angiography; n=30) CAD.  The levels of interleukin-1β (IL-1β) and interleukin 6 (IL-6) were measured in plasma using enzyme  immunoassay.Results. IL-6  levels were significantly higher in patients with obstructive  CAD  (p=0.006) than in patients with non-obstructive CAD.  There were no significant  differences  in the level of IL-1β in both groups  (p=0.482). When  constructing the ROC  curve,  the threshold  value of IL-6  was  26.060 pg/ml. At the level of IL-6  less than this value, CAD  was diagnosed with hemodynamically insignificant stenoses of the coronary  arteries.Conclusion. The results of this study confirm that in patients with different types of coronary  artery lesions, there are differences  in the activity of the inflammation process in the arterial wall. IL-6  was higher in the obstructive  lesion group,  and IL-1β levels did not differ between groups.  Thus, it can be assumed  that hemodynamically significant  obstruction  of the coronary  arteries develops  as a result of highly  active inflammation of the vascular wall. Given the presence of a proven biological  basis and the available data on the effectiveness of monoclonal antibodies to IL-1β, one cannot exclude their possible benefit in a cohort of patients with CAD  and hemodynamically insignificant stenoses.